A modeling study of secondary organic aerosol formation from sesquiterpenes using the STOCHEM global chemistry and transport model. Issue 8 (19th April 2017) - Khan, M. A. H.; Jenkin, M. E.; Foulds, A.; Derwent, R. G.; Percival, C. J.; Shallcross, D. E.
Abstract: Sesquiterpenes are one of the precursors of secondary organic aerosol (SOA) which can be an important global sources of organic aerosol (OA). Updating the chemistry scheme in the global chemistry transport model by incorporating an oxidation mechanism for β‐caryophyllene (representing all sesquiterpenes), adding global sesquiterpene emissions of 29 Tg/yr, and revising global monoterpene emissions up to 162 Tg/yr [ Guenther et al., 2012] led to an increase of SOA burden by 95% and SOA production rate by 106% relative to the base case described in Utembe et al. [2011]. Including the emissions of sesquiterpenes resulted in increase of SOA burden of 0.11 Tg and SOA production rate of 12.9 Tg/yr relative to the base case. The highest concentrations of sesquiterpene‐derived SOA (by up to 1.2 μg/m 3 ) were found over central Africa and South America, the regions having high levels of biogenic emissions with significant biomass burning. In the updated model simulation, the multigeneration oxidation products from sesquiterpenes and monoterpenes transported above the boundary layer and condensed to the aerosol phase at higher altitude led to an increase of OA by up to 30% over the tropics and northern midlatitude to higher altitude. The model evaluation showed an underestimation of model OA mostly for the campaigns dominated by regional anthropogenic pollution. The increase of SOA production from sesquiterpenes reduced the discrepancies between modeled and observed OA concentrations over the remote and rural areas. The increase of SOA concentrations by up to 200% from preindustrial to present scenarios was found over the tropical oceans. Key Points: Updating the SOA module of the STOCHEM‐CRI chemistry scheme by incorporating a detailed oxidation mechanism of β‐caryophyllene The addition of sesquiterpenes increases the SOA global burden and production rate by 0.11 Tg and 12.9 Tg/yr, respectively Globally, up to 1.2 μg/m 3 sesquiterpene‐derived SOA were seen over central Africa and South America